2019
DOI: 10.1177/0004865819846944
|View full text |Cite
|
Sign up to set email alerts
|

Pride and prejudice: Exploring how identity processes shape public attitudes towards Australian counter-terrorism measures

Abstract: Counter-terrorism measures are often described as pre-emptive, punitive, and afford authorities exclusive and expanded powers. Yet they continue to attract public support (Huddy, Feldman, Taber, & Lahav, 2005; Welch, 2016). Why is this the case? A consistent finding in traditional crime control research shows a link between perceived threat from racial or ethnic minority groups and their perceived involvement in crime. This perceived relationship results in public support for punitive crime control measures fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Terrorism laws are therefore applied more frequently to Muslim defendants in Australia. Additionally, the media and governments in Australia and elsewhere continue to state that there is a persistent threat of Islamic extremism to global security (Williamson et al, 2019). This notion is reinforced by governmental responses such as the proscription regime, whereby to date only terrorist organizations with an Islamic ideology have been proscribed as terrorist organizations by the Australian Government (Lynch, et al, 2015).…”
Section: Counterterrorism and Muslim Communities In Australiamentioning
confidence: 99%
See 3 more Smart Citations
“…Terrorism laws are therefore applied more frequently to Muslim defendants in Australia. Additionally, the media and governments in Australia and elsewhere continue to state that there is a persistent threat of Islamic extremism to global security (Williamson et al, 2019). This notion is reinforced by governmental responses such as the proscription regime, whereby to date only terrorist organizations with an Islamic ideology have been proscribed as terrorist organizations by the Australian Government (Lynch, et al, 2015).…”
Section: Counterterrorism and Muslim Communities In Australiamentioning
confidence: 99%
“…However, scant research exists in the counter-terrorism context (for exceptions see Piazza, 2015;Welch, 2016;Williamson, 2019). We are aware of only two published studies that have directly identified a positive relationship between perceiving Muslims as a threat and subsequent support for punitive counter-terrorism policies.…”
Section: Racial Animus Perceptions Of Threat and Support For Punitive Punishment Policymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that majority-group members, who perceive Muslims as a threat, as being religious and as supporting or being associated with terrorism, are more supportive of institutional WHAT MAKES A TERRORIST? 25 discrimination, anti-immigration policies or extraordinary detention practices among others (Doosje et al, 2009;Piazza, 2015;Welch, 2016;Williamson, 2019;Williamson & Murphy, 2020). Our research extends this work by comparatively testing the influence on both punitive and social policy support.…”
Section: Discussionmentioning
confidence: 60%